Efektivitas Pendidikan Kesehatan Media Video Terhadap Pengetahuan dan Sikap Tentang Anemia pada Remaja Putri - Rista Yunanda; Lani Gumilang; Neneng Martini; Fardila Elba; Ari Indra Susanti (Berita Kedokteran Masyarakat (BKM), 2019)
Background: Anemia in adolescent girls reduces motoric development, mentality, and intelligence and affects adolescent girl health in the future. Lack of hemoglobin may cause some complications in pregnancy and childbirth. Thereby, health education is needed to prevent anemia. Retention of information through video is 30%. Purpose: This study investigates the effectiveness of health education using video in improving knowledge and attitude regarding anemia among adolescent girls. Method:  This study used quasi-experimental with one group pretest-posttest design. Fifty-three adolescent girls studying at SMAN 1 Tasikmalaya were recruited in this study as selected through Proportionate Stratified Random Sampling. Data analysis used the Wilcoxon Signed Rank Test for knowledge data and the Paired Sample T-Test for attitude data. Pearson's Correlation Coefficient R Formula calculated the effect size. Results:  The results showed improved knowledge and attitude scores after giving health education using video (p-value, < 0.05 ). The effect size of the knowledge variable was 0.87, and the attitude variable was 0.74. Conclusion:  health education using video has a large effect in improving knowledge and attitude regarding anemia among adolescent girls.Keywords: Anemia, Attitude, Adolescent Girls, Health Education, Knowledge